Exploring suicidal attempts in a rare case of Klinefelter syndrome comorbid with autism spectrum disorder: unveiling the underdiagnosed nexus and noble intervention of electroconvulsive therapy - Ridzwan, Hijaz; Ariff, Khadijah; Abdul Razak, Afidatul Hanim; Tengku Kamarulbahri, Tengku Mohd Saifuddin (Wolters Kluwer Health, 2024)
Klinefelter syndrome (KS) is a rare genetic disorder that may present concomitantly with autism spectrum disorder (ASD). This case report details the unique clinical presentation of a 24-year-old male diagnosed with both KS and ASD, characterized by a series of multiple suicidal attempts. This case sheds light on the underdiagnosed nature of KS, emphasizing the intricate interplay between hereditary variables and mental vulnerability. Notably, the patient’s clinical trajectory took an unexpected turn with the successful application of electroconvulsive therapy, suggesting a promising intervention for individuals facing similar challenges. This report contributes to the growing body of literature on the intersectionality of genetic conditions and psychiatric disorders, highlighting the importance of recognizing and addressing these complexities in clinical practice.